Peningkatan Kesejahteraan Keluarga Melalui Financial Health Warga Kebun Melati Jakarta Pusat - Winaya Purwanti; Achmad Jaelani; Karsam; Hastuti Indra Sari (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
The low level of household financial management literacy is one of the key factors hindering the improvement of family welfare, particularly among low- to middle-income urban communities. Observations of residents in RW 04, Kebun Melati Subdistrict, Central Jakarta, indicate the persistence of high consumptive spending, limited saving habits, the absence of emergency funds, and a tendency to use consumptive debt through digital lending platforms. These conditions contribute to low levels of household financial stability. This Community Service Program (PkM) aims to improve family financial health through the implementation of a Community-Based Financial Health Model supported by training and mentoring in budgeting, healthy debt management, emergency fund development, routine saving behavior, and simple digital financial recording. The implementation methods include interactive workshops, case simulations, coaching sessions, and monitoring of financial behavior changes. The results show improvements in residents’ ability to prepare household budgets, a reduction in consumptive spending, an increase in ownership of savings and emergency funds, and the establishment of Community Financial Ambassadors as sustainability agents of the program. A comparison of pre- and post-program conditions indicates improved financial literacy, enhanced financial discipline, and growth in household financial assets. This program provides novelty through the development of an applicable and sustainable community-based financial health model.